2020
DOI: 10.1186/s13041-020-00568-7
|View full text |Cite
|
Sign up to set email alerts
|

Circadian expression of Fabp7 mRNA is disrupted in Bmal1 KO mice

Abstract: The astrocyte brain-type fatty acid binding protein (Fabp7) gene expression cycles globally throughout mammalian brain, and is known to regulate sleep in multiple species, including humans. The mechanisms that control circadian Fabp7 gene expression are not completely understood and may include core circadian clock components. Here we examined the circadian expression of Fabp7 mRNA in the hypothalamus of core clock gene Bmal1 knockout (KO) mice. We observed that the circadian rhythm of Fabp7 mRNA expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…These results support activation of astrocytes as a general feature of CNS model systems with knockout of Bmal1, since a modest upregulation of Fabp7 transcripts in the hypothalamus of global Bmal1 knockout mice was recently reported (Gerstner & Paschos, 2020), whereas the relation between a knockout of BMAL1 and activation of GFAP-positive astrocyte has been previously reported both in vitro and in vivo (Lananna et al, 2018;Musiek et al, 2013).…”
Section: Gfap-and Fabp7-positive Cells Are Abundant In the Cerebral C...supporting
confidence: 83%
“…These results support activation of astrocytes as a general feature of CNS model systems with knockout of Bmal1, since a modest upregulation of Fabp7 transcripts in the hypothalamus of global Bmal1 knockout mice was recently reported (Gerstner & Paschos, 2020), whereas the relation between a knockout of BMAL1 and activation of GFAP-positive astrocyte has been previously reported both in vitro and in vivo (Lananna et al, 2018;Musiek et al, 2013).…”
Section: Gfap-and Fabp7-positive Cells Are Abundant In the Cerebral C...supporting
confidence: 83%
“…It regulates fatty acid uptake in astrocytes, sleep (Gerstner et al, 2017) and drug seeking under stressful conditions (Hamilton et al, 2018). Fabp7 is rhythmically expressed throughout the brain (Schnell et al, 2014) and is similarly upregulated in Arntl and Nr1d1 knock-out mice (Schnell et al, 2014;Gerstner and Paschos, 2020). Fabp7 could be upregulated in Npas2 mutants because of the downregulation of Nr1d1, which represses Fabp7 (Schnell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alongside sleep disturbance, another mechanism that may influence FABP7-signaling in AD is disruption of the circadian system. Circadian expression of Fabp7 is regulated by the core-clock gene BMAL1 ( Gerstner and Paschos, 2020 ) and the circadian transcriptional repressor REV-ERBα (NR1D1) ( Vanderheyden et al, 2021 ) and exhibits time-of-day changes at the tripartite synapse ( Gerstner et al, 2012b ). Many studies in humans and in animal models have shown a link between the circadian clock and AD ( Weldemichael and Grossberg, 2010 ; Cermakian et al, 2011 ; Musiek and Holtzman, 2016 ; Homolak et al, 2018 ; Wu et al, 2019 ; Lananna and Musiek, 2020 ; Carter et al, 2021 ; Fusilier et al, 2021 ; Nassan and Videnovic, 2022 ).…”
Section: Alzheimer’s Disease Fabp7 and The Circadian Clockmentioning
confidence: 99%